Diagnosis from Tissue: Histology and identification-Quiz the expert session - Q14 - Sabino, Raquel (2022)
Histopathology continues to be a rapid and cost-effective means of providing a presumptive or definitive diagnosis of invasive fungal infections. Tissue samples from patients with suspected invasive fungal disease (IFD) should be examined not only by mycological culture but also by microscopy and specific fungal stains should be included. For histopathological diagnosis of fungal infection is required deep knowledge about fungal morphology in tissue and also about the various reactions of the tissue in response to that infection. Highly experienced histopathologists are therefore essential to detect fungal structures and also to recognize tissue reactions associated with IFD, distinguishing them from staining artifacts. Histopathology of specimens obtained from an affected site, showing a positive result by the presence of distinctive structures associated to specific endemic fungal species, is considered as criteria for proven IFD. On the other hand, observation of yeasts may sometimes point out for a specific IFD but without confidence. Examination of filamentous fungi in histopathological sections can provide important information like the presence of septa, the hyphal diameter or branching angle and melanisation and may thus yield valuable diagnostic clues on the nature of the causative agent. However, a reliable identification of the fungal species based solely on morphological criteria in histopathology is usually impossible. Species identification of fungi detected in histopathological sections should be attempted using immunohistochemical and/or molecular tools. The recently revised EORTC/MSG criteria for diagnosis of IFD from tissue specimens recommends the amplification of fungal DNA by PCR combined by DNA sequencing only when fungal elements are seen by histopathology. During this presentation we will discuss with the audience, in an interactive mode, the advantages and pitfalls of tissue diagnosis, and which tests that can be performed to a more targeted diagnosis.